Three delays model applied to pediatric injury care seeking in Northern Tanzania: A mixed methods study - Elizabeth M. Keating; Francis Sakita; Blandina T. Mmbaga; Ismail Amiri; Getrude Nkini; Sharla Rent; Nora Fino; Bryan Young; Catherine A. Staton; Melissa H. Watt (Public Library of Science (PLoS), 2022)
Pediatric injuries are a leading cause of morbidity and mortality in low-and middle-income countries. Timely presentation to care is key for favorable outcomes. The goal of this study was to identify and examine delays that children experience between injury and receiving definitive care at a zonal referral hospital in Northern Tanzania. Between November 2020 and October 2021, we enrolled 348 pediatric trauma patients, collecting quantitative data on referral and timing information. In-depth interviews (IDIs) to explain and explore delays to care were completed with a sub-set of 30 family members. Data were analyzed according to the Three Delays Model. 81.0% (n = 290) of pediatric injury patients sought care at an intermediary facility before reaching the referral hospital. Time from injury to presentation at the referral hospital was 10.2 hours [IQR 4.8, 26.5] if patients presented first to clinics, 8.0 hours [IQR 3.9, 40.0] if patients presented first to district/regional hospitals, and 1.4 hours [IQR 0.7, 3.5] if patients presented directly to the referral hospital. In-hospital mortality was 8.2% (n = 30); 86.7% (n = 26) of these children sought care at an intermediary facility prior to reaching the referral hospital. IDIs revealed themes related to each delay. For decision to seek care (Delay 1), delays included emergency recognition, applying first aid, and anticipated challenges. For reaching definitive care (Delay 2), delays included caregiver rationale for using intermediary facilities, the complex referral system, logistical challenges, and intermediary facility delays. For receiving definitive care (Delay 3), wait time and delays due to treatment cost existed at the referral hospital. Factors throughout the healthcare system contribute to delays in receipt of definitive care for pediatric injuries. To minimize delays and improve patient outcomes, interventions are needed to improve caregiver and healthcare worker education, streamline the current trauma healthcare system, and improve quality of care in the hospital setting.